Rock / water / life : ecology & humanities for a decolonial South Africa - Green, Lesley, 1967- (Duke University Press, 2020)
"ROCK / WATER / LIFE bridges personal and theoretic registers, telling stories that lay bare the shared genealogy of environmental conservation and institutionalized racism in South Africa. Through her narrative and thick description of the terrain, Lesley Green makes clear the political stakes of environmental humanism and the authoritarian uses of environmental science. Green herself operates at the juncture of these fields, seeking to determine whether science itself might be a space for the necessary work of decolonizing the Anthropocene. In reclaiming ecological thought from a too-frequent separation from its historical and political economic context, Green asks what a decolonial South African ecological philosophy might look like and provides some of the tools necessary to approach alternative forms of praxis. Her work calls for a trenchant reappraisal of science as it manifests in environmental and economic exclusions, and for new engagements with the human/non-human entanglements that might provide a new means of inclusion. The book itself comprises several such possible interventions to create space for a critical inquiry into the South African scientific/educational establishment. Following a foreword by Isabelle Stengers, Green's three organizing forms (rock, water, and life) reappear to frame these sites of inquiry. The first three chapters offer sites at which scientific certainty was presented to shore up and perpetuate the colonial project. For instance, chapter 2 discusses how the belief that use of cement might adequately protect against the consequences of fracking mirrors similar faith in the state's regulatory systems. Comparatively, the latter three chapters then explore the possibilities in environmental and ecological thought that could disrupt the colonial and modernist frames that hamper the decolonization of life in the Anthropocene. Here, chapter 5 introduces a call for a decolonized primatology in recognition of the role of simianization and criminalization in South African history. It is through this structure that Green draws several distinct provocations into relation: calls to decolonize, to operationalize recent work in political ontology, to further a cosmopolitical critique of neoliberalism, and to interrogate the loss of trust in Science. This project will be of interest to readers in anthropology, environmental studies, environmental humanities, cultural studies, and human geography, as well as gaining readers in the philosophy and history of science, feminist anthropology, feminist STS, eco-feminism, the Anthropocene, and decolonialist thought. The book might also gain a broader readership with those interested in matters of education, race, inequality, and conservation in South Africa"--